Cysteic Acid-Modified Glassy Carbon Electrode for Monitoring Oxalic Acid (Oa) Concentration During Its Electrochemical Oxidation at Ti/Pt Anode - Salazar-Gonzalez, R (Wiley-VCH Verlag, 2014)
The aim of this manuscript is to develop a combined method for the detection and elimination of oxalic acid (OA) in aqueous environment. For that, the surface of glassy carbon (GC) electrode has been modified by oxidation of L-cysteine using cyclic voltammetric (CV) technique. After modification, the formation of a compact and uniform cysteic acid layer film was achieved and it was confirmed by surface analysis (scanning electron microscopy (SEM) and atomic force microscopy (AFM)). Estimation of the linear range, calibration function and limit of detection for OA were performed by differential pulse voltammetry using Cysteine-modified electrode (Cysteine-MGC). Due to its stability and sensitive response to OA, it was used for monitoring OA during its electrochemical oxidation at Ti/Pt anode. DPV analyses have been compared with classic titration method and HPLC achieving a good fit, confidence intervals and limits. The results are described and discussed in the light of the existing literature. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.